2016
DOI: 10.4000/samaj.4226
|View full text |Cite
|
Sign up to set email alerts
|

Of Slums and Politics in Puri, Odisha: The Localisation of the Slum-Free Cities Mission in the Temple City

Abstract: This paper results from my doctoral research at ETH Wohnforum-ETH CASE, ETH Zürich, Department of Architecture. The dissertation, which is in its concluding stage, is concerned with the nature of contemporary urban development in India and the role of urban policy therein. In particular, the emphasis is on the role of slum re-development in remaking Indian medium-sized cities. The first three years of the project were funded by a Sawiris Scholarship (now referred to as E4D Doctoral Scholarships, see https:// w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This research implicitly challenges researchers to engage with the multiplicity of groups that intervene in and shape governance and to consider their source(s) of legitimacy and authority. In turn, to recognise the importance of locality, and of spatial practices, that produces disciplinary space within Indian cities (Donner and De Neve, 2006a; Hagn, 2016). This research has demonstrated the importance of capturing the contingent and variable nature of governance networks in order to construct a nuanced analysis of governmental power in the everyday.…”
Section: Understanding Everyday Governancementioning
confidence: 99%
“…This research implicitly challenges researchers to engage with the multiplicity of groups that intervene in and shape governance and to consider their source(s) of legitimacy and authority. In turn, to recognise the importance of locality, and of spatial practices, that produces disciplinary space within Indian cities (Donner and De Neve, 2006a; Hagn, 2016). This research has demonstrated the importance of capturing the contingent and variable nature of governance networks in order to construct a nuanced analysis of governmental power in the everyday.…”
Section: Understanding Everyday Governancementioning
confidence: 99%